Equilibrium studies and dynamic behavior of cadmium and copper adsorption onto palm oil fly ash - Abdul Aziz, Abdul Shukor (2014)
Over the past century, human activities have led to severe environmental degradation especially heavy metals contamination. The role of adsorption using agricultural by-products has been critically investigated in order to develop cheaper and more effective natural adsorbents for the removal of heavy metals from wastewater. Therefore, in this present study, the adsorption performance and characteristics of palm oil fly ash (POFA) were investigated for the removal of Cd(II) and Cu(II) from aqueous solution. The studies were conducted using batch and fixed-bed column experiments and the characterization of the POFA was determined through BET, SEM/EDX and FT−IR analysis. A series of batch adsorption studies were conducted with the effects of relevant parameters such as contact time, initial solution pH, adsorbent dosage and initial metal ions concentration. Fundamental batch study indicated that 80% of Cd(II) and Cu(II) were removed in the first 30 minutes of agitation. Meanwhile, both Cd(II) and Cu(II) uptake mechanism were particularly pH- and concentration-dependant, favoring a pH value of 7 and 6 respectively. The experimental data were analyzed using the Langmuir, Freundlich and Temkin isotherm models. The adsorption behavior of Cd(II) and Cu(II) fitted well to the Langmuir isotherm, with a maximum monolayer adsorption capacity of 15.82 and 17 mg/g respectively. The applicability of the Langmuir isotherm suggested the formation of monolayer coverage of metal ions onto equivalent sites of the adsorbent. Kinetics experimental data followed the trend of pseudo second-order kinetics, which was consistent with chemisorptions with intraparticle diffusion involved as one of the rate determining step. The performance of continuous fixed-bed columns study for the adsorption of Cd(II) and Cu(II) onto POFA were described through the concept of breakthrough curve under relevant operating conditions such as adsorbent bed depths and influent metal concentrations. Results showed that the breakthrough time increases with increasing bed depth, and decreases as the influent metal concentration increases. The Cd(II) and Cu(II) uptake mechanism were particularly bed depth- and concentration-dependant, favouring higher bed depth and lower influent metal concentration. The maximum uptakes of Cd(II) and Cu(II) in a fixed-bed column at bed depth of 2 cm and influent metal concentration of 20 mg/L were found to be 34.91 and 21.93 mg/g, respectively. The column experimental data were analyzed using the bed depth service time (BDST), Thomas, and Yoon–Nelson models. The Thomas and Yoon–Nelson models were successfully applied in describing the dynamic behavior of the adsorption process, indicating that both models were very compatible for the POFA column design over a range of feasible bed depths and concentrations. However, the initial region of the breakthrough curve for Cd(II) adsorption was better described using the BDST model. Conclusively, this study indicates that POFA could be used successfully as a natural low-cost adsorbent for the removal of Cd(II) and Cu(II) from aqueous solution.